Responsibility of Land Deed Making Officials (PPAT) for Making Deeds of Sale and Purchase of Joint Property Objects Transferred Without the Consent of the Wife - Ayu, Sheila Hanifa Rosi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims to analyze: 1) The legal consequences of making a deed of sale and purchase of joint property objects transferred without the wife's consent. 2) The responsibility of the land deed making official (PPAT) for making a deed of sale and purchase of joint property objects transferred without the wife's consent. The approach method used in this study is the case study approach and the statutory approach. This type of research is qualitative research. The type and source of data in this study are secondary data obtained through literature studies. The analysis in this study is qualitative. The results of the study concluded: 1) The legal consequences of making a deed of sale and purchase of joint property objects transferred without the wife's consent are invalid or null and void, because the making of the deed of sale and purchase before the PPAT is not based on honest intentions. This also results in the PPAT being involved in an unlawful act. A deed of sale and purchase that is declared to have no binding legal force results in the deed becoming an underground deed, and the sale of the land becomes invalid or null and void. This causes losses to the parties, especially in this case the Buyer. With the cancellation of the sale and purchase transaction, the sale and purchase transaction is considered to have never occurred so that the status of the land should return to its original state. 2) The responsibility of the land deed making official (PPAT) for making a deed of sale and purchase of joint property objects transferred without the wife's consent is an absolute responsibility caused by the PPAT being less careful and cautious in making the deed of sale and purchase. As in Article 1366 of the Civil Code, everyone is responsible not only for losses caused by their actions, but also for losses caused by their negligence or lack of caution. By stating that the deed of sale and purchase is contrary to the law, it will cause losses for the buyer, so that the PPAT must also be responsible for the material losses suffered by the parties.Keywords: Deed; Joint; Property; Purchase.